2000
DOI: 10.1097/00000542-200004000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Fentanyl with Xenon to Block Somatic and Hemodynamic Responses to Surgical Incision

Abstract: Comparing these results with previously published results in the presence of 70% nitrous oxide, the fentanyl requirement in xenon anesthesia is smaller than that in the equianesthetic nitrous oxide anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 26 publications
1
14
0
3
Order By: Relevance
“…[1][2][3] In addition to its analgesic potency, 4 xenon has also been shown to possess significant cardioprotective and neuroprotective capacity. [5][6][7] Because of these organ-protective characteristics, interest in xenon has been propagated.…”
mentioning
confidence: 99%
“…[1][2][3] In addition to its analgesic potency, 4 xenon has also been shown to possess significant cardioprotective and neuroprotective capacity. [5][6][7] Because of these organ-protective characteristics, interest in xenon has been propagated.…”
mentioning
confidence: 99%
“…[4] In clinical anesthesia, as there is no specific indicator for nociceptive-antinociceptive balance, anesthesiologists use isolated nonspecific autonomic responses (HR and BP) as the end points in anesthetizing surgical patients. [15] Laryngoscopy and endotracheal intubation are an integral part of general anesthesia to secure the airway, whereas change of position (prone position) and skin incision are the requirements for surgical access.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that xenon has an analgesic action similar to that of N 2 O [18][19][20][21] and that xenon has a greater analgesic effect than sevoflurane. The concentration of fentanyl necessary to prevent a hemodynamic response in 50% of patients at 0.7 MAC is 0.94 ng/mL with xenon [22] and 1.8 ng/mL with sevoflurane [23], and the ratio of MAC-awake-MAC is 0.46 with xenon and 0.35 for sevoflurane [24]. Hence, the analgesic effect of xenon can be an important factor in the suppression of the catecholamine and hemodynamic responses.…”
Section: Discussionmentioning
confidence: 99%